(The Effect of Distillation Time on Citronellal Content Of Citronellal Oil) - Moestafa, A; Pudjiastuti, Untari (Balai Besar Industri Agro, 1987)
Effect of distillation time on citronellal content of citronella oil has been studied. Two kinds of raw materials were used, one from old plantation at Rumpin Kabupaten Bogor and the other from Batutulis Kecamatan Kota Bogor Selatan. It is showed that most oil were distilled at the early stage of destillation along with the citronellal component. Grass from Rumpin should be destilled for no longer than two hours to obtain enough oil (yield 94%) and citronellal content not less than 35.5%. The grass from Batutulis produced more oil after two hours distillationÂ (95%) and the average citronellal content is 49.70%. The grass from Batutulis may be distilled up to 4 hours to gain more or less than 100% oil while the citronellal content still at higher level (48%). Obviously the grass from Batutulis is better than Rumpin.